Rendimiento de la especie Calycophyllum spruceanum (capirona) en función a la calidad de las trozas y tipología de la madera aserrada, en la empresa Agroforestal Requena S.A.C., Iquitos, 2022 - Isern Yancan, Diego Orlando (2023)
This study was carried out at the Wood processing plant at the AGROFORESTAL REQUENA S.A.C sawmill, located on SantaMaria-Iquitos, Loreto Road, a company dedicated to sawing and planning wood, owned by Nery Evelio Hernández, with the purpose of determining the yield of the species Calyphyllum (Capirona) according to the quality of the logs and typology of the sawn wood in the company Agroforestal Requena S.A.C. From the obtained results, it is found that the quality “A” of the logs of the species Calyphyllum (Capirona) reaches 81.48% of the total logs (54) with 56.53 m3 of volumen and that in terms of percentage corresponds to 82.35 volume in first quality. The second quality was 18.51% of the total logs with a volumen of 12.12 m3. The yield in the log and sawn wood ratio was 68.64% with a volumen of 47.28 m3 and waste of 31.039%. Yield by category was 27.3 m3 with 57.74% for commercial longwood, 10.39 m3 with 21.98% for narrow longwood, 5.52 m3 with 11.68% for shortwood and 4.31 m3 with 9.12% for shortwood. The alternative hypothesis is accepted since there is a close relationship between the yield in volumen and typology of the sawn wood of the Capirona species and the quality of the logs (ha).